2021
DOI: 10.1007/s11123-021-00600-5
|View full text |Cite
|
Sign up to set email alerts
|

World agricultural convergence

Abstract: The goal of this article is to answer two questions: Has world agricultural convergence occurred? If not, how can this goal be fulfilled? This article introduces a model averaging method to consider both a parametric and a semi-parametric SFA model to better estimate technical efficiency. Then, three types of convergence tests are employed to check if world agricultural catch-up occurs and to determine the degree of convergence across different groups of countries. The empirical results on a balanced panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Shang (2015) reviews the family of model averaging methods and uses the jackknife method to study the productivity of 112 countries over the period from 1960-2012. Gong (2020a) adopts the jackknife method to predict agricultural productivity in China, while Yuan et al (2021) uses this approach to estimate world agricultural efficiency.…”
Section: Aggregation Method: Single-to Multi-dimensional Analysismentioning
confidence: 99%
“…Shang (2015) reviews the family of model averaging methods and uses the jackknife method to study the productivity of 112 countries over the period from 1960-2012. Gong (2020a) adopts the jackknife method to predict agricultural productivity in China, while Yuan et al (2021) uses this approach to estimate world agricultural efficiency.…”
Section: Aggregation Method: Single-to Multi-dimensional Analysismentioning
confidence: 99%
“…Comprehensive analysis of multiple emergy indicators can better reveal the quality of sustainable intensification of agroecological economic systems. In view of this, we refer to Baráth and Fertő [ 32 ] and Yuan et al [ 33 ] for a comprehensive measure of the intensity of agricultural sustainability in China using three comprehensive indicators: (1) emergy yield rate (EYR), the greater the value, the greater the contribution of external resources to create available resources; (2) environmental loading rate (ELR), a larger ELR indicates that agricultural production uses more non-renewable resources relative to renewable resources; and (3) emergy sustainability index (ESI), the higher the value, the greater the sustainable development capability. The variables are defined in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have studied convergence in agriculture, for example, Yuan et al (2021), which analyse whether world agricultural convergence can be observed. The authors use a model averaging method to consider both a parametric and a semiparametric stochastic frontier model to better estimate technical efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%